Boy, can he dance! - Spinelli, Eileen; Yalowitz, Paul (New York : Aladdin Paperbacks, 1997)
Although his father wants him to follow the family tradition and become a chef, a young boy would much rather dance.
Booklist.
Kirkus Review.
Publisher's Weekly.
3.6
K-3
Keywords: Dance -- Fiction; Fathers and sons -- Fiction; Occupations -- Fiction; Dancing -- Fiction; Father-son relationship -- Fiction; Occupations -- Fiction